As transformações no cenário eleitoral decorrentes do surgimento das novas tecnologias : na campanha de José Ivo Sartori para o governo do RS em 2014 - Manfredini, Rodolfo Soares (2017)
The present work presents an analysis of the perceived changes in the political area, due to the advent of new technologies. The electoral campaign of José Ivo Sartori for the government of Rio Grande do Sul in 2014 was chosen for the study, as he successfully exploited the use of the Internet and its technological developments. Thus, a little known candidate of the majority of the population, managed to win the elections becoming governor of the state. Three points will be analyzed, since innovative strategies have been considered: the hashtag: # SartorãoDaMassa; Sartori's request to voters, made during Free Election Time (FET), to record videos with open arms, simulating a hug the size of Rio Grande; and the testimony of Sartori's mother, also broadcast on FET.